Use of in vivo transit portal images to detect gross inter-fraction patient geometry changes on an O-ring type linear accelerator for pelvis and head/neck patients. (25th October 2021) - Aland, Trent; Jarema, Talia; Spalding, Myles; Kairn, Tanya; Trapp, Jamie
Abstract: The purpose of this work was to investigate the use of the Varian Portal Dosimetry application in conjunction with in vivo megavoltage portal images on a Varian Halcyon O-ring type linear accelerator as an in vivo dosimetry constancy (IVDc) tool for pelvis and head/neck patients receiving VMAT treatments. Sensitivity testing was conducted on phantoms with varying thicknesses (0.2 cm–1.0 cm) using static and modulated fields. A cohort of 96 portal dose images across eight patients was then compared with PTV metrics derived from daily CBCT image based treatment plan re-calculations to determine whether the IVDc tool could detect gross inter-fraction anatomical changes. A final cohort of 315 portal dose images across 22 patients was then assessed to demonstrate the application of IVDc tool. The IVDc tool, using 2%/2 mm criteria, detected all phantom thickness changes of 1.0 cm, some phantom thickness changes of 0.5 cm, and no changes of 0.2 cm. For the cohort of 96 results, a IVDc passing criteria of 95% (2%, 2 mm) was able to identify all cases that had PTV metric changes of 2% or more. Using the IVDc tool on the cohort of 315 results, and the IVDc passing criteria of 95%, resulted in 74 IVDc failures. A simple, easy to implement, methodology has been presented that is capable of detecting gross inter-fraction changes in patient geometry on the Varian Halcyon O-ring linac linear accelerator.